MODEL PENGEMBANGAN KINERJA DOSEN BERBASIS ORGANIZATIONAL HAPPINESS CHARACTER: Suatu Studi PTS se-Bandung Raya - Granit Agustina, - (2023)
ABSTRAK Granit Agustina (1907456), "Model Pengembangan Kinerja Dosen Berbasis Organizational Happiness Character" (Suatu studi PTS Se-Bandung Raya). Disertasi Doktor Ilmu Manajemen Sekolah Pascasarjana Universitas Pendidikan Indonesia, Dibawah bimbingan Prof. Dr. H. Eeng Ahman, M.S., Prof. Dr. H. Disman, M.S., Prof. Dr. Dra. Hj. Janah Sojanah, M.Si. Penelitian ini menganalisis model pengembangan kinerja dosen berbasis organizational happiness character pada Perguruan Tinggi Swasta (PTS) se-Bandung Raya. Tujuan penelitian ini adalah mendeskripsikan manajemen talenta, organizational happiness character, komitmen organisasi, organizational citizenship behavior dan kinerja dosen serta mengukur pengaruh manajemen talenta, organizational happiness character, komitmen organisasi, organizational citizenship behavior terhadap kinerja dosen. Penelitian ini dilakukan dengan menggunakan metode verifikatif dan explanatory survey dengan pendekatan kuantitatif. Unit analisis penelitian ini adalah PTS se-Bandung Raya dengan dosen sebagai unit observasi. Jumlah populasi sebesar 5.434 dari 21 PTS dengan sampel sebanyak 385 dosen. Data diperoleh dari hasil survey melalui kuesioner yang disebar kepada dosen PTS. Analisa data menggunakan statistik deskriptif dan Structural Equation Modelling (SEM) dengan Analysis of Moment Structure (AMOS). Hasil penelitian menunjukan bahwa manajemen talenta, organizational happiness character, komitmen organisasi dan organizational citizenship behavior di lingkungan PTS se-Bandung Raya berada pada kategori tinggi sedangkan kinerja dosen berada pada kategori cukup tinggi. Pengujian hipotesis membuktikan manajemen talenta, organizational happiness character, komitmen organisasi dan organizational citizenship behavior berpengaruh positif terhadap kinerja dosen. Komitmen organisasi dan organizational citizenship behavior memediasi pengaruh manajemen talenta dan organizational happiness character terhadap kinerja dosen. Novelty penelitian ini adalah model peningkatan kinerja dosen melalui strategi penerapan komitmen organisasi dan organizational citizenship behavior berbasis organizational happiness character (OHC) PTS se-Bandung Raya. Terdapat beberapa kelemahan pada setiap dimensi pada setiap variabel yang masih harus ditingkatkan. Kata Kunci: Manajemen talenta, organizational happiness character, organizational citizenship behavior, komitmen organisasi, kinerja dosen, PTS Se-Bandung Raya. ABSTRACT Granit Agustina (1907456), "Lecturer Performance Development Model Based on Organizational Happiness Character" (Studies in the Greater Bandung Private universities). Doctoral dissertation in Management Science at the Graduate School of the University of Indonesia, Under the guidance of Prof. Dr. H. Eeng Ahman, M.S., Prof. Dr. H. Disman, M.S., Prof. Dr. Dra. Hj. Janah Sojanah, M.Si. This study analyzes the model of developing lecturer performance based on the character of organizational happiness in private universities (PTS) throughout Greater Bandung. The purpose of this study was to describe talent management, the character of organizational happiness, organizational commitment, organizational citizenship behavior and lecturer performance and to measure the influence of talent management, organizational happiness character, organizational commitment, organizational citizenship behavior on lecturer performance. This research was conducted using a verification and explanatory survey method with a quantitative approach. The unit of analysis for this research is PTS throughout Bandung Raya with lecturers as the unit of observation. The total population is 5,434 from 21 PTS with a sample of 385 lecturers. Data were obtained from survey results through questionnaires distributed to PTS lecturers. Data analysis used descriptive statistics and Structural Equation Modeling (SEM) with Structural Moment Analysis (AMOS). The results showed that talent management, organizational happiness character, organizational commitment and organizational citizenship behavior at private tertiary institutions in Bandung Raya were in the high category while lecturer performance was in the fairly high category. Testing the hypothesis proves that talent management, the character of organizational happiness, organizational commitment, and organizational citizenship behavior have a positive effect on lecturer performance. Organizational commitment and organizational citizenship behavior mediate the influence of talent management and the character of organizational happiness on lecturer performance. The novelty of this research is a model of improving lecturer performance through a strategy for implementing organizational commitment and organizational citizenship behavior based on organizational happiness (OHC) characters at private tertiary institutions in Bandung Raya. There are several weaknesses in each dimension of each variable that still need to be improved. Keywords: Talent management, organizational happiness character, organizational citizenship behavior, organizational commitment, lecturer performance, Greater Bandung Private universities.